Can't decide how much to EAT? Effort variability for reward is associated with cognitive restraint. (1st April 2021) - van den Hoek Ostende, Mechteld M.; Neuser, Monja P.; Teckentrup, Vanessa; Svaldi, Jennifer; Kroemer, Nils B.
Abstract: Food intake is inherently variable and often characterized by episodical restraint or overeating (uncontrolled eating). Such heightened variability in intake has been associated with higher variability in the brain response to food reward, but it is an open issue whether comparable associations with elevated variability in reward seeking exist. Here, we assessed whether restraint and uncontrolled eating as markers of trait-like variability in eating are associated with higher intra-individual variability in reward seeking as captured by a cost-benefit paradigm. To test this hypothesis, 81 healthy, overnight-fasting participants ( M BMI  = 23.0 kg/m 2  ± 3.0) completed an effort allocation task (EAT) twice. In the EAT, participants had to exert physical effort to earn monetary and food rewards and indicated levels of wanting through visual analog scales (VAS). As predicted, we found that greater trial-by-trial effort variability was associated with lower scores on cognitive restraint, r p (78) = −0.28, p  = .011 (controlled for average effort). In line with previous findings, higher wanting variability was associated with higher BMI, r p (78) = 0.25, p  = .026 (controlled for average effort). Collectively, our results support the idea that higher variability in reward seeking is a potential risk factor for eating beyond homeostatic need. Since associations with variability measures of reward exceeded associations with average reward seeking, our findings may indicate that variability in the representation of the reward value could be a crucial aspect driving fluctuations in food intake.